(untitled) (Conference Zone, 2022)
The article considers that one of the urgent tasks of the existing education system is to bring education in line with world standards. The ways of introducing a credit-modular system into the education system based on European standards are described. Methods used in the training of technology teachers on a credit-modular system in higher education, including the sequence of developing a materials science program. When creating a scientific program, its features were taken into account. The advantages of the credit-modular system in higher education are also described and recommendations are given.